Pengaruh Penerapan Metode WAFA terhadap Kemampuan Tajwid Siswa Kelas VI SD Muhammadiyah 01 Tanggul Tahun Pelajaran 2025/2026 - Yolanda Dwintarisma Andrini; Eka Sri Ruminingsih; Samsiyah Nuril Hidayah; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to investigate the effect of the implementation of the WAFA Method on the tajweed proficiency of Year 6 students at SD Muhammadiyah 01 Tanggul during the 2025/2026 academic year. The background of this research stems from the generally low level of tajweed skills among students in reading the Qur’an, particularly in the articulation of letters (makhraj) and the application of recitation rules (ahkam al-tajweed). The WAFA Method was chosen because it combines the talaqqi, musyafahah, and tilawah bil nagham approaches, which emphasise active student engagement through repeated practice in reading, listening to, and imitating the teacher's recitation. This approach is believed to improve phonetic accuracy and students’ understanding of tajweed more effectively than conventional methods. The study employed a quantitative approach using a quasi-experimental design, specifically the Nonequivalent Control Group Design model. The sample consisted of two parallel classes with a total of 48 students, in which the experimental class was taught using the WAFA Method while the control class received instruction through conventional methods. Data were collected via tajweed proficiency tests administered before and after the intervention (pre-test and post-test). Data analysis was conducted using an Independent Samples T-Test with SPSS version 25 to determine the significance of differences between the two groups. The results showed that the application of the WAFA Method had a positive and significant effect on students’ tajweed skills. The experimental class showed an average improvement of 15.66 points, while the control class improved by only 2.08 points. The t-test yielded a value of t = -8.399 with a significance level of Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant difference between the two groups. These findings demonstrate that the WAFA Method is effective in enhancing letter pronunciation accuracy, the application of recitation rules, and students’ fluency in reading the Qur’an. Therefore, the WAFA Method is a viable alternative strategy for Qur’anic instruction at the primary school level, contributing to the development of a generation capable of reciting the Qur’an tartil, in accordance with the rules of tajweed.